Upaya Pemberian Makanan Tambahan (PMT) Pada Balita Gizi Kurang Untuk Mencegah Stunting Di Desa Kalirejo - Aria Afif; Nabilla Jasmine; Nadifa Afni Azizah; Shafira Friesilia Putri; Anggun Tri Mawardani; Taufikurrahman (Jurnal Penelitian Multidisiplin, 2023)
Cases of undernutrition in toddlers are a serious problem in Indonesia. Toddlers with poor nutritional status are at risk for growth and development both physically and intellectually. The government together with the Ministry of Health has issued a policy to reduce the number of children under five with undernourished status to stunting with the Supplemental Feeding Program (PMT). This research was conducted to determine the effectiveness of exclusive 14-day supplementary feeding (PMT) to 8 toddlers with undernourished status in Kalirejo Village, Dringu District, Probolinggo District, by providing assistance in the form of Supplementary Feeding (PMT) and monitoring by measuring body weight and toddler height with poor nutritional status. This study uses a qualitative descriptive method to explain a series of mentoring and monitoring processes to the results obtained. From this study, the results obtained were that 6 out of 8 children experienced weight gain and height, while the other 2 experienced weight loss.